CARM1 inhibition reduces histone acetyltransferase activity causing synthetic lethality in CREBBP/EP300 mutated lymphomas - Veazey, Kylee J. (Leukemia, 2020)
Somatic mutations affecting CREBBP and EP300 are a hallmark of Diffuse Large B Cell Lymphoma (DLBCL). These mutations are frequently monoallelic, within the histone acetyltransferase (HAT) domain and usually mutually exclusive, suggesting that they might affect a common pathway and their residual WT expression is required for cell survival. Using in vitro and in vivo models, we found that inhibition of CARM1 activity (CARM1i) slows DLBCL growth and that the levels of sensitivity are positively correlated with the CREBBP/EP300 mutation load. Conversely, treatment of DLBCLs that do not have CREBBP/EP300 mutations with CARM1i and a CBP/p300 inhibitor revealed a strong synergistic effect. Our mechanistic data show that CARM1i further reduces the HAT activity of CBP genome wide and downregulates CBP target genes in DLBCL cells, resulting in a synthetic lethality that leverages the mutational status of CREBBP/EP300 as a biomarker for the use of small molecule inhibitors of CARM1 in DLBCL and other cancers.